Final answer:
a. The complete ionic equation for the reaction is K+(aq) + C2O42-(aq) + Ba2+(aq) + 2OH-(aq) --> Ba2+(aq) + C2O42-(aq). The net ionic equation is Ba2+(aq) + C2O42-(aq) --> BaC2O4(s). b. The complete ionic equation for the reaction is Pb2+(aq) + 2NO3-(aq) + 2H+(aq) + SO42-(aq) --> PbSO4(s). The net ionic equation is Pb2+(aq) + SO42-(aq) --> PbSO4(s). c. The complete ionic equation for the reaction is CaCO3(s) + H2SO4(aq) --> CaSO4(s) + CO2(g) + H2O(l). The net ionic equation is CaCO3(s) + H2SO4(aq) --> CaSO4(s) + CO2(g) + H2O(l).
Step-by-step explanation:
a. K+(aq) + C2O42-(aq) + Ba2+(aq) + 2OH-(aq) → Ba2+(aq) + C2O42-(aq)
Net ionic equation: Ba2+(aq) + C2O42-(aq) → BaC2O4(s)
b. Pb2+(aq) + 2NO3-(aq) + 2H+(aq) + SO42-(aq) → PbSO4(s)
Net ionic equation: Pb2+(aq) + SO42-(aq) → PbSO4(s)
c. CaCO3(s) + H2SO4(aq) → CaSO4(s) + CO2(g) + H2O(l)
Net ionic equation: CaCO3(s) + H2SO4(aq) → CaSO4(s) + CO2(g) + H2O(l)